(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
The period up to eight years is considered to be the peak time for brain development. From birth to about the age of eight the brain is a super-sponge. This is the brain’s most absorbent stage, where it actively learns from its environment. “Windows of opportunity” are sensitive periods in children’s lives when specific types of learning take place. Information flows easily into the brain through ’windows’ that are open for only a short duration. Then the ’windows’ close, and much of the fundamental architecture of the brain is completed. Scientists are continually learning more about how young children’s brains develop. At the same time, teachers are looking for effective strategies to help children use their brains to their fullest capacity. This paper also contributes to this dialogue by summarizing what we already know about the learning process in the brain and suggests how it might form the teaching and learning process in the classroom.